The roles of natural killer cells in bone and arthritic disease: a narrative review - Yiming Zhao; Qian Liu; Jinmin Zhao; Dezhi Song (Immunological Medicine)
The skeletal system is responsible for the body’s support and motor functions, and can be pathologically affected by factors, such as metabolism, autoimmune inflammation, tumors, and infections. Regarding tissue localization and biological function, the immune system is deeply involved in the physiological and pathological processes of the skeletal system. As a regulator and effector cell of the innate immune system, natural killer (NK) cells can exert cytotoxic effects through cell contact and immunomodulatory effects through cytokine secretion. In the past 30 years, many advances have been made regarding the role of NK cells and their derived cytokines on bone and joints. In this review, the role of NK cells in the physiological activities of bone remodeling is summarized first, focusing on osteoclast differentiation and function. Subsequently, the roles of NK cells in osteoarthritis, bone tumors, and bone diseases caused by microbial infections are described, meanwhile, some conflicting research results are discussed. By reviewing the state-of-the-art progress of NK cells in the above-mentioned bone physiological and pathological processes, it is helpful to clarify the blind spots of current research and provide some references for the integrated evaluation of immune factors in the study of skeletal system diseases.